MO723: Ankle-Brachial Index is Associated with Subendocardial Viability Ratio in Chronic Hemodialysis Patients. (3rd May 2022) - Piko, Nejc; Bevc, Sebastjan; Hojs, Radovan; Petreski, Tadej; Knehtl, Masa; Ekart, Robert
Abstract: BACKGROUND AND AIMS: Ankle-brachial index (ABI) is a marker of peripheral arterial disease and is associated with increased cardiovascular morbidity and mortality. Structural alterations in the arterial walls lead to functional central haemodynamic changes, potentially impacting pulse wave reflection and, consequently, myocardial perfusion. The aim of this study was to determine the association between ABI and subendocardial viability ratio (SEVR) as a non-invasive measure of coronary perfusion in chronic haemodialysis patients. METHOD: We measured ABI using an automated non-invasive waveform analysis device (MESI®, Slovenia) and SEVR using applanation tonometry (Sphygmocor, Atcor Medical, Sydney, Australia). All the measurements were performed on a non-dialysis day and SEVR on the non-arteriovenous fistula (non-AVF) hand. ABI was calculated as the ratio between systolic blood pressure on the non-AVF hand and systolic blood pressure on the calves of both legs. Mean ABI of both sides was used in the statistical analysis. RESULTS: A total of 29 patients (mean age 63.6 ± 10.5 years, 69.0% male) were included. In Table 1, descriptive parameters are presented. Of those, 4 patients (13.8%) have an ABI <0.9 and the other 25 patients (86.2%) have a normal ABI between 0.9 and 1.3. Using the independent-samples T-test, patients with a lower ABI have a statistically significant lower SEVR compared with patients with normal ABI (109 versus 142%; P = 0.039). CONCLUSION: Low ABI is independently associated with decreased subendocardial perfusion in chronic haemodialysis patients, suggesting that both methods of ABI and SEVR measurement may reflect an atherosclerotic process in peripheral and coronary arteries.